Influence of rainfall and temperature on biomass production of Pennisetum purpureum clones - ?lvarez, Adri?n; Herrera, Rafael; D?az, Laisaury; Noda, Aida Carmelita (Cuban Journal of Agricultural Science, 2013)
Biomass production performance of nine Pennisetum purpureum clones was evaluated in function of air temperature, rainfall and number of rainy days. The research was based on an experimental study developed at the Institute of Animal Science during the period 2009-2010 in a typical red ferrallitic soil without applying fertilization or irrigation. A completely randomized design was used and nine cuttings with four replications were practiced. Average yields of the two years of evaluation were 2.32 ? 4.08 t/ha in the rainy period which were higher to those obtained in the dry period (0.75 ? 1.36 t/ha). Yield had a decreasing tendency in time The highest significant correlations were achieved with the temperature (0.33-0.70) besides the number of rainy days. The coefficients of determination ranged between 58 and 80 %. It is concluded that forage production of P. purpureum was connected with the performance of the rainfall and temperature, and constitute a viable alternative for biomass production. Key words: without fertilization or irrigation, yield, climatic variables